2018
DOI: 10.1111/ajt.14723
|View full text |Cite
|
Sign up to set email alerts
|

Increasing tacrolimus time-in-therapeutic range is associated with superior one-year outcomes in lung transplant recipients

Abstract: Calcineurin inhibitors (CNIs) are the backbone of traditional immunosuppressive regimens for lung transplant recipients (LTR). The CNIs are both narrow therapeutic index drugs with significant interpatient and intrapatient variability that require therapeutic drug monitoring to ensure safety and effectiveness. We hypothesized that tacrolimus time-in-therapeutic range (TTR) affects acute and chronic rejection rates in LTRs. This was a single-center, observational, cross-sectional study of 292 adult LTRs. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 19 publications
5
44
1
Order By: Relevance
“…These observations were consistent with the findings from previous kidney transplant and lung transplant analyses, which used the TTR to characterized tacrolimus exposure (11,12). Notably, we did not find any difference in mean tacrolimus trough level between the high and low TTR groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These observations were consistent with the findings from previous kidney transplant and lung transplant analyses, which used the TTR to characterized tacrolimus exposure (11,12). Notably, we did not find any difference in mean tacrolimus trough level between the high and low TTR groups.…”
Section: Discussionsupporting
confidence: 92%
“…The warfarin TTR cut-off value was arbitrarily determined as 75% (10) or was recommended by European guidelines as being 70% or greater (18). Two studies investigating the use of tacrolimus TTR also arbitrarily set the TTR threshold as 30% in lung transplant (11) or 60% in kidney transplant (12). Although they found that increasing tacrolimus TTR was associated with improved clinical outcomes, the optimal TTR was not determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize its efficacy and minimize the occurrence of adverse events, therapeutic drug monitoring (TDM) is regularly performed in clinical practice on the basis of trough concentration (C0) levels that are determined before the next dose of tacrolimus . C0 has been selected as a measure of systemic exposure that correlates with clinical outcome (graft rejection and tacrolimus toxicity) . However, C0‐based therapeutic ranges in children are defined based on empirical adaptation of the doses according to the C0 from adult clinical data …”
mentioning
confidence: 99%
“…(1) C0 has been selected as a measure of systemic exposure that correlates with clinical outcome (graft rejection and tacrolimus toxicity). (3) However, C0-based therapeutic ranges in children are defined riva et al…”
mentioning
confidence: 99%